Role of motivation and well-being indicators in interventions to improve well-being at work among primary care physicians: a systematic review - Adriana Flórez; Esperanza Villar-Hoz (BMJ Open)
Objective The well-being of primary care physicians (PCPs) has become an object of concern for governments due to staff shortages and high staff turnover. The objective of this study was to carry out a systematic review of individualised interventions aimed at improving the well-being of PCPs, which allowed us to determine (1) the type of interventions being carried out; (2) the well-being indicators being used and the instruments used to assess them; (3) the theories proposed to support the interventions and the mechanisms of action (MoA) put forward to explain the results obtained and (4) the role that individual motivation plays in the interventions to improve well-being among PCPs.Design Systematic review.Eligibility criteria Clinical trials on interventions aimed at improving the well-being of PCPs.Information sources: a search of studies published between 2000 and 2022 was carried out in MEDLINE/PubMed, SCOPUS and Web of Science (WOS).Results From the search, 250 articles were retrieved. The two authors each reviewed the articles independently, duplicate articles and those that did not meet the inclusion criteria were discarded. A total of 14 studies that met the criteria were included: 6 randomised clinical trials, 4 controlled clinical trials and 4 unique cohorts, with a before-and-after assessment of the intervention, involving a total of 655 individuals participating in the interventions. A meta-analysis was not possible due to the heterogeneity of the studies.Conclusions The information evaluated is insufficient to accurately assess which outcomes are the best indicators of PCPs well-being or what role plays in the individual motivation in the results of the interventions. More studies need to be carried out on the subject to determine the MoA of the different interventions on the results and the motivation of the participating PCPs.